Curious George's are you curious? - Rey, H. A. (Hans Augusto), 1898-1977. (Boston : Houghton Mifflin, 1998)
Curious George illustrates a variety of emotions and states of being, including happy, proud, dizzy, naughty, silly, and, of course, curious.
Title from cover.
On board pages.
Keywords: Monkeys -- Fiction; Emotions -- Fiction